Andreev reflection in two-dimensional topological insulators with either conserved or broken time-reversal symmetry - SANVITO, STEFANO; NARAYAN, AWADHESH (My University, 2012)
We investigate Andreev reflection in two-dimensional heterojunctions formed by a superconductor in contact with a topological insulator ribbon either possessing or breaking time-reversal symmetry. Both classes of topological insulators exhibit perfect Andreev reflection, which is robust against disorder. This is assigned to topologically protected edge states. In the time-reversal symmetric case we show that doping one of the ribbon edges with magnetic impurities suppresses one Andreev channel, while no such suppression is seen in the broken symmetry situation. Based on this observation, we suggest a tabletop transport experiment able to distinguish between the two types of topological insulators, which does not involve the direct measurement of the material band structure.
PUBLISHED
Keywords: Andreev reflection; Nanoscience & Materials